Hölder Continuity of Solutions to Parametric Generalized Vector Quasiequilibrium Problems - Z. Y. Peng (Abstract and Applied Analysis)
By using a linear scalarization method, we establish sufficient conditions for the Hölder continuity of the solution mappings to a parametric generalized vector quasiequilibrium problem with set-valued mappings. These results extend the recent ones in the recent literature, (e.g., Li et al. (2009), Li et al. (2011)). Furthermore, two examples are given to illustrate the obtained result.